Caracterização da escama de tilápia (Oreochromis niloticus) e avaliação do seu potencial de sorção de íons Cu(II) - Bazarin, Guilherme (2015)
This study objectives was to characterize the tilapia fish scales (Oreochromis niloticus), assess their potential of Cu (II) ions removal and investigate how occurs retention of these ions by biosorbent. Was also evaluated the influence of chemical treatments with hydrochloric acid (HCl) and sodium hydroxide (NaOH) in scales biosorption capacity. The scales, collected from a fish slaughterhouse in the city of Marechal Cândido Rondon - PR, has been washed with water until constant pH, dried in oven, some of these scales was subjected to treatment with HCl and some with NaOH. The characterization of the scale was performed by techniques the gas He pycnometry, N2 physiosorption, SEM, EDS, FT-IR, FT-Raman and pHZPC. Experiments were performed in closed batch system to examine the effect of the initial pH of solution (1, 2, 3, and 4), temperature (20, 30 and 40 °C), stirring speed (80, 100 and 150 rpm) and the chemical treatments. Finally, equilibrium assays were performed at the optimum conditions obtained. The characterization showed the in natura scales are natural composites, showing the presence of chemical groups characteristic of collagen and hydroxyapatite, indicated incidence of micropores on the scale surface, but with very small volume, and also that there is a morphological and chemical difference between the inner side (smooth side) and external side (rough side). The scales has density of 1,8 g cm-3, surface area of 2,0 m2 g-1, zeta potential of -4,1 mV e pHZPC of 4,3. Chemical pretreatments did not change the surface area, density and the pHZPC but indicated zeta potential reduces, causing weight loss of 20.5% in the treatment with HCl and 8.9% in the treatment with NaOH, and showed a decrease in biossorption capacity of Cu (II) ions. The batch adsorption process reached higher values of adsorption capacity in pH 3, temperature of 30°C and stirring speed of 100 rpm. The pseudofirst order model has shown the best fit to the kinetic data. Langmuir isotherm best represented the equilibrium data of batch process with calcutated qmáx (0,762 mEq g-1) very close of the experimental value (0,757 mEq g-1), showing 95% removal with only 1 g biosorbent. The biossorption process of Cu (II) ions occurs by more than one mechanism, being the main one the ion exchange with Ca (II) ions. Thus, we can say that the scales of tilapia (Oreochromis niloticus) used in natura and whole are an alternative adsorbent potential due to low cost and efficient removal of Cu (II).